Landrace Diversity and Production Systems of Cowpea (Vigna unguiculata L. Walp.) in Southern Chad - Djirabaye, Nadjiam (International Journal of Applied Sciences and Biotechnology, 2021)
In Chad, cowpea (Vigna unguiculata (L.) Walp.), is increasingly becoming a cash crop. The objective of this work is to assess the varietal diversity, analyze the traditional management of landraces and the production systems of cowpea in southern part of Chad. An inventory and an ethnobotanical survey was conducted through a participatory approach in 17 villages corresponding to two agro ecological zones. Thirty-four vernacular names and 45 landraces are inventoried. On average, 2 names are assigned per village. The number of landraces varies from 4 to 13 with an average of 9.00 per region and 2.70 per village. The highest diversity is observed in Mayo Kebbi. Sixteen morphotypes have been identified and their distribution varies according to the agro ecological zones. Productivity (31.10 %), taste (25.92 %) and grain size (18.34 %) are the farmer main preferred criteria. Farmers use leaves (47 %), pods (29.50 %) and seeds (14.75 %) to identify landraces. Cowpea cultivation is practiced on small areas and in intercropping system (78.60 %). Conservation of seeds (36.07 %), low fertility of the soils (27.85 %) and drought (17.77 %) were the main production constraints. Cowpea is stored mainly in traditional granaries (34.96 %) and on racks (22.93 %). For seeds treatment, farmers use mainly traditional means (32.37 %) and chemical products (6.67 %). Several cowpea-based dishes are identified. Cowpea has also therapeutic virtues. To improve cowpea production, appropriate actions must be considered against the constraints inventoried. The interesting landraces should also be used in a breeding program. Int. J. Appl. Sci. Biotechnol. Vol 9(3): 176-186.